Permeation Resistance of Sawdust Ash Blended Cement Laterized Concrete - Samuel Olufemi Folagbade; Aluko Olawale (Institute of Research and Community Outreach - Petra Christian University, 2019)
This paper compared the initial surface absorption of conventional concrete and laterized concrete containing Portland cement (PC) and sawdust ash (SDA). Laterized concrete was produced at laterite contents of 15 and 30% as partial replacement for sand and SDA contents of 10 and 20% as partial replacement for PC. Compressive strengths at 28 days and initial surface absorption after 10 minutes (ISA-10) at 28, 60 and 90 days were determined at the water/cement ratios of 0.35, 0.50 and 0.65 and assessed at equal 28-day strengths of 25-35 N/mm2. At equal water/cement ratios, compressive strength reduced and ISA-10 increased with increasing content of laterite and SDA. On the other hand, compressive strength and resistance to surface absorption of the blended cement laterized concretes increased with increasing curing age. At equal strengths, all the blended cement laterized concretes have better resistance to surface absorption than the conventional PC concrete.